2019
DOI: 10.1038/s41598-019-48585-4
|View full text |Cite
|
Sign up to set email alerts
|

Shootins mediate collective cell migration and organogenesis of the zebrafish posterior lateral line system

Abstract: The zebrafish sensory posterior lateral line is an excellent model system to study collective cell migration and organogenesis. Shootin1 is a cytoplasmic protein involved in neuronal polarization and axon guidance. Previous studies have shown that shootin1 couples actin filament retrograde flow with extracellular adhesive substrates at the leading edge of axonal growth cones, thereby producing mechanical force for the migration and guidance of axonal growth cones. However, the functions of shootin in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Recent studies have reported that the molecular clutch system involving shootin1a, cortactin, and L1 mediates axon guidance in response to the diffusible chemotactic ligand netrin-1 ( 34 ) and the substrate-bound haptotactic ligand laminin ( 31 ). The clutch molecule shootin1 is also involved in the generation of force for neuronal migration ( 77 , 78 ) and required for axon pathfinding and cell migration in vivo in three-dimensional environments ( 34 , 77 , 79 ). Netrin-1 signals promote Pak1-mediated shootin1a phosphorylation in axonal growth cones under the activation of Cdc42 and Rac1 ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that the molecular clutch system involving shootin1a, cortactin, and L1 mediates axon guidance in response to the diffusible chemotactic ligand netrin-1 ( 34 ) and the substrate-bound haptotactic ligand laminin ( 31 ). The clutch molecule shootin1 is also involved in the generation of force for neuronal migration ( 77 , 78 ) and required for axon pathfinding and cell migration in vivo in three-dimensional environments ( 34 , 77 , 79 ). Netrin-1 signals promote Pak1-mediated shootin1a phosphorylation in axonal growth cones under the activation of Cdc42 and Rac1 ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, shootin1 KO results in ectopic accumulation of mitral cells ( Minegishi et al, 2018 ), olfactory excitatory neurons that undergo radial migration ( Hinds, 1968 ; Blanchart et al, 2006 ). Recent studies also reported that shootin1 knockdown inhibits the radial migration of cortical neurons ( Sapir et al, 2013 ) and that shootin1 KO delays the collective cell migration of zebrafish posterior lateral line primordium (PLLP), a cluster of progenitor cells destined to form a mechanosensory organ called the neuromast ( Urasaki et al, 2019 ). These data suggest that traction force generated by shootin1-mediated actin–adhesion coupling may propel the migration of multiple types of neurons.…”
Section: Forces For Leading Process Extensionmentioning
confidence: 99%